Effect of age on fattening and body condition of draught oxen fed teff straw (Eragrostis teff) based diets - Osuji, P.O.; Capper, B. (Springer, 1992)
Twenty four Ethiopian highland Zebu (Bos indicus) oxen were allocated to 6 groups of 4 animals each on the basis of liveweight, age and body condition. The animals were group-fed an experimental diet consisting of 551g/kg concentrate and 449 g/kg teff straw, at the rate of 2.5 kg per 100 kg of liveweight for 18 weeks. They were weighed and condition scored weekly. Feeding levels were adjusted weekly. The daily liveweight gain of each animal was estimated and changes in condition score evaluated. Age significantly affected the liveweight gains and body condition score changes of the oxen. There was a significant effect of age on average liveweight gain. The average daily gains were 0.62, 0.51 and 0.41 kg/day for animals aged 4 to 5, 7 to 8 and 10 to 11 years respectively. Age exhibited a significant effect on body condition changes. The results are discussed in terms of benefits from traction and fattening and farm system implications of fattening younger animals for reproduction and improved feeding.